THE ADVANTAGES OF USING REALIA IN TEACHING VOCABULARY - Narbekov , Farhod Nuriddinovich (Educational Research in Universal Sciences, 2023)
The article deals with a contemporary issue of importance – that of teaching vocabulary using realia